The Best Marketing 4.0 Brand Model in Indonesia - Ardiansyah, Tedy; Zulfikar, Ian; Awaloedin, Dipa Teruna (Future Science / FSH-PH Publications, 2022)
The purpose of this study is to find out the best marketing 4.0 brand model in Indonesia, not just a brand that is a symbol of the current development of technology or industry 4.0. Marketing is a major part of the progress of a company, along with the development of technology, marketing becomes the main problem of survival of a company. Marketing 4.0 is the right answer in helping to solve these problems, especially in building a company brand. But how to build the right Marketing 4.0 so that the brand becomes the main breath of the company. The method used is a qualitative case study method, which describes in detail a program. The results of this study show an invention for the best Marketing 4.0 brand model in Indonesia, so it is expected to be a model for the company's progress in this 4.0 industry.